Comparative Study of Performance between International Roughness Index (IRI), Pavement Condition Index (PCI), and Bina Marga Method on Roadways - St Maryam H; Bulgis Bulgis; Rustam Madami (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
In this research, a comparative study is conducted between the International Roughness Index (IRI), Pavement Condition Index (PCI), and Bina Marga method on roadways with a flexible pavement structure. The objective is to compare the results of road damage evaluation using these three methods and formulate appropriate treatment programs. The research findings indicate that overall, the IRI method provides an overview of the road surface roughness level. The majority of the analyzed data falls under the "Moderate" category with a value of 7.2. The PCI method measures the physical condition of the road infrastructure, which is categorized as "Fair" with a value of 41.2. On the other hand, the Bina Marga method assesses the type of road maintenance, which is categorized as "Routine Maintenance" with a value of 6.8. Enhancing road maintenance practices is necessary to address minor damages such as small cracks or surface irregularities that affect road user comfort.